Liguria - Cavallo, Maria Caterina; Cipriani, Filippo; Gerzeli, Simone; Demarteau, Nadia; Marocco, Alessia; Bamfi, Francesco (Farmeconomia. Health economics and therapeutic pathways, 2008)
In Liguria region 66% of women (aged 25-64) are screened regularly, meaning every 3 years. Considering regional tariffs and vaccine acquisition cost, the vaccination of 12-year-old girls with a 90% coverage could prevent 22 cases of cervicocarcinoma and 9 related deaths and thus results to be cost-effective (24.584 €/QALY). When the vaccination programme is extended to 16-year-old girls a further 23 cancer cases and 10 deaths could be prevented, with a very similar cost-effectiveness ratio. In Liguria region, the net cost for woman vaccinated is 183 € for the single cohort and 186 € for the multiple cohort.